2005
DOI: 10.1212/01.wnl.0000184498.16959.c0
|View full text |Cite
|
Sign up to set email alerts
|

Perception of facial expression and facial identity in subjects with social developmental disorders

Abstract: The processing of facial identity and that of facial expression are dissociable in social developmental disorders. Deficits in perceiving facial expression may be related to emotional processing more than face processing. Dissociations between the perception of facial identity and facial emotion are consistent with current cognitive models of face processing. The results argue against hypotheses that the social dysfunction in social developmental disorder causes a generalized failure to acquire face-processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 46 publications
3
20
1
Order By: Relevance
“…Further discussion of the details of these diagnostic criteria can be found in our previous reports on this cohort. 49,51 A substantial number of our subjects fulfilled criteria for both Asperger disorder and social-emotional processing disorder. Subjects were classified as meeting criteria for Asperger disorder only (n ϭ 2), social-emotional processing disorder only (n ϭ 11), both Asperger disorder and social-emotional processing disorder (n ϭ 8), or high-functioning autism (n ϭ 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further discussion of the details of these diagnostic criteria can be found in our previous reports on this cohort. 49,51 A substantial number of our subjects fulfilled criteria for both Asperger disorder and social-emotional processing disorder. Subjects were classified as meeting criteria for Asperger disorder only (n ϭ 2), social-emotional processing disorder only (n ϭ 11), both Asperger disorder and social-emotional processing disorder (n ϭ 8), or high-functioning autism (n ϭ 3).…”
Section: Discussionmentioning
confidence: 99%
“…These subjects have had extensive testing of their face perception, which has been reported previously. 49,51 These include standard neuropsychological instruments such as the Warrington Recognition Memory test, 52 and the Benton Face Recognition test, 53 as well as our own experimental tests of discrimination of famous from anonymous faces, 54 and of facial imagery. 55 (In addition, the averaged upright configuration perception data from this report were also presented in one of these prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate explanation must also account for Box 2. Questions for future research † Are the various difficulties observed in face processing in individuals with ASD (failure to attend to the eyes; reduced holistic/configural processing; difficulties with identity, expressions, gender, eye gaze) part of the same underlying problem or are they independent and dissociable [78]?…”
Section: Does the Perceptual Deficit Extend To Other Classes Of Visuamentioning
confidence: 99%
“…Researchers have hypothesized that the social dysfunctions in social developmental disorders, such as autism, impair the acquisition of normal face-processing skills (Hefter, Manoach, & Barton, 2005). Indeed, Dawson, Webb and McPartland (2005) have demonstrated that individuals with autism have impaired face discrimination and recognition, and use atypical strategies for processing faces characterized by reduced attention to the eyes and piecemeal rather than configural strategies.…”
Section: Social Cognition Involving Face and Gazementioning
confidence: 99%